Real time kinematic satellite navigation of a hexarotor unmanned aerial vehicle - Wang, Tao (2017)
The Unmanned Aerial Vehicle (UAV) has been used commonly nowadays. More and more research institutes and companies spent a lot of money on it. In some fields, locating precisely the position of the UAV has become a significant issue. Traditional Global Positioning System (GPS) could guarantee the location of the UAV in meter precision. But this precision for UAV’s application is not enough. A more precise locating system Real Time Kinematic (RTK) which uses Global Navigation Satellite System (GNSS) will be a better choice. The accuracy is around 1-2cm horizontally or vertically. Hence, this project will focus on to achieve this accuracy. Through researching RTKLIB, using Raspberry PI and NVS receiver cards combined with the RTKLIB to conduct experiments. As expected, the result of this method is excellent and it is practical to use this in UAV application such as Search & Rescue and Express Delivery. This project consists of two parts namely the RTK Base station and Rover station. The Base station is the main station that sends correction data to the Rover station for use in real time and post processing later. Using corrections Rover station can compute the number (ambiguity integer) of wavelengths between the satellite and the Rover station. Combining with common estimation method such as Kalman filter, it can calculate this integer and finally get the accurate location. Finally, the best test conducting on the top of parking garage under a clear sky, when the UAV is stable, the average positioning accuracy can achieve 1 cm, when it is moving, the average positioning accuracy is 5 cm.